“Reality rarely looks like the guidelines”: a qualitative study of the challenges hospital-based physicians encounter in war wound management - Andreas Älgå; Karin Karlow Herzog; Murad Alrawashdeh; Sidney Wong; Hamidreza Khankeh; Cecilia Stålsby Lundborg (Scandinavian Journal of Trauma, Resuscitation and Emergency Medicine, 2018)
Abstract Background Globally, armed conflict is a major contributor to mortality and morbidity. The treatment of war-associated injuries is largely experience-based. Evidence is weak due to difficulty in conducting medical research in war settings. A qualitative method could provide insight into the specific challenges associated with providing health care to injured civilians. The aim of this study was to explore the challenges hospital-based physicians encounter in war wound management, focusing on surgical intervention and antibiotic use. Methods Semi-structured, face-to-face interviews were conducted with physicians at a Jordanian hospital supported by Médecins Sans Frontières. The interviews were recorded, transcribed verbatim and analysed using content analysis with an inductive and deductive approach. Results We found that challenges in war wound management primarily relate to protocol adherence. Protocols for the management of acute war wounds were adhered to on areas that could be considered commonly agreed principles of war wound surgery, such as the use of wound debridement and the evaluation of the systemic condition of the patient before initiating antibiotic treatment. We identified limitations imposed on the physicians that complicate or even hinder protocol adherence. Additionally, we identified factors associated with conscious deviations from the protocols. Conclusions We conclude that adherence to established protocols around the management of acute war wounds is difficult. We present aspects that may be considered when establishing clinical projects in similar contexts. The knowledge gained by this study could provide insights for the development of protocols or guidelines for wound management and antibiotic use in an unstable setting, such as a hospital in close proximity to armed conflict. We suggest the use of a grounded theory approach to further study the discrepancy between guideline recommendations and actual practice.